When Psychology Meets Pedagogy: Interdisciplinary Perspectives on Moral Extremism and Emotional Trauma in David Fincher’s Se7en - Harwanto, Aditya Putra; Fauzi, Muhammad Fariz; Thariq, Muhammad Hafizh; Alkatami, Laden (Peradaban Journal of Interdisciplinary Educational Research, 2025)
This study addresses the representation of moral extremism and emotional trauma in David Fincher’s Se7en, situating the film not merely as a cinematic spectacle but as a discursive arena that engages forensic psychology, moral pedagogy, and ethical philosophy. The primary aim is to analyze how psychological and pedagogical dimensions frame the phenomenon of moral extremism embodied by the antagonist, while also tracing the traumatic repercussions for other characters and the wider social context. Using a literature-based methodology, this research integrates theories of emotional psychology, critical pedagogy, and moral thought with film analysis as a cultural text. The findings reveal that Se7en not only exposes the destructive face of absolute morality but also highlights the emotional scars left by radical ethical claims, thereby creating a subtle pedagogical space for audiences to reflect on the urgency of humanistic and inclusive moral education. This study recommends the integration of forensic psychology and moral pedagogy into curricular design and public discourse to strengthen awareness of the dangers of ethical absolutism and to foster emotional resilience. Its novelty lies in the interdisciplinary approach that bridges film studies, psychology, pedagogy, and philosophy, opening new horizons in understanding cinema as a medium of moral and educational reflection. Kajian ini membahas representasi ekstremisme moral dan trauma emosional dalam film Se7en karya David Fincher, dengan menempatkan film tersebut bukan sekadar sebagai tontonan sinematik, melainkan sebagai arena diskursif yang melibatkan psikologi forensik, pedagogi moral, dan filsafat etika. Tujuan utama penelitian ini adalah menganalisis bagaimana dimensi psikologis dan pedagogis membingkai fenomena ekstremisme moral yang diwujudkan oleh tokoh antagonis, sekaligus menelusuri dampak traumatis yang dialami karakter lain maupun konteks sosial yang lebih luas. Dengan menggunakan metode kajian pustaka, penelitian ini mengintegrasikan teori psikologi emosional, pedagogi kritis, dan pemikiran moral dengan analisis film sebagai teks budaya. Temuan menunjukkan bahwa Se7en tidak hanya menyingkap wajah destruktif dari moralitas absolut, tetapi juga menyoroti luka emosional yang ditinggalkan klaim etis yang radikal, sehingga membuka ruang pedagogis yang halus bagi audiens untuk merenungkan urgensi pendidikan moral yang humanis dan inklusif. Studi ini merekomendasikan integrasi psikologi forensik dan pedagogi moral ke dalam desain kurikulum maupun wacana publik guna memperkuat kesadaran terhadap bahaya absolutisme etis sekaligus menumbuhkan ketahanan emosional. Kebaruan penelitian ini terletak pada pendekatan interdisipliner yang menghubungkan kajian film, psikologi, pedagogi, dan filsafat, sehingga membuka cakrawala baru dalam memahami sinema sebagai medium refleksi moral dan pendidikan.